Enhancing electrochemical performance of nickel nanostructured coatings via ultrasonic-assisted electrodeposition with SiC nanoparticle incorporation - Norouzi Heravan, Hossein; Zandi, Yousef (Journal of Composites and Compounds, 2025)
In this study, nickel (Ni) nanostructure coating and Ni/ silicon carbide (SiC) nanocomposite coating were produced by electroplating method under ultrasonically-pulse current on the stainless steel substrate. The presence of SiC nanoparticles in the Ni matrix caused a change in the preferred orientation from the (200) plane to the (111) plane. The electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests were carried out after 1 h in 3.5% NaCl solution. The results of polarization showed that due to the presence of SiC ceramic nanoparticles on the surface of the coating, the corrosion resistance increased by reducing the active metal surface. This was attributed to the neutral nature of the ceramic particles in the corrosive solution. The polarization resistance for the composite coating increased by 61 % compared to pure Ni. Also, the corrosion rate for composite coating compared to pure Ni decreased from 0.0055 to 0.013 mm/year. Vickers microhardness for the composite sample increased by 45 % compared to pure Ni. The Young's modulus for the composite sample increased by 46%.